Non-Communicable Diseases (NCDs) Information System - Farid Agushybana; Cahya Tri Purnami; Dharminto (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2023)
Non-communicable diseases (NCDs) are the leading cause of death worldwide. In Indonesia, NCDs has increased and shifted patterns. Changes in behavior and lifestyle increase the risk of NCDs. Difficulties in monitoring treatment and patient visits are a challenge for health workers. Currently, there is still no integrated information system for patient monitoring. The general objective of this research is to develop an integrated Non-Communicable Disease Information System (NCDSI) in Semarang City. The current study uses the Rapid Application Development (RAD) method with a qualitative approach. RAD is a complete approach model for information system development and covers the entire system life cycle. This research was conducted in three stages: planning and needs analysis, designing, developing, and collecting feedback. During the development and collection of feedback, functionality testing activities are carried out to obtain feedback and evaluation as the system is improved. The research was carried out by the Semarang City Office. The functional test subjects consisted of three agents and five patients with primary hypertension and diabetes mellitus. The results: the planning and needs analysis phases were carried out through thorough interviews with end-users. The system design phase was described through contextual diagrams and database tables, and the development and feedback phase was conducted through the NCDSI functionality test. Conclusion: The developed NCDSI has been integrated and has four user levels (users of the City Health Office, Head of Puskesmas, Cadres, and patients).